Disparities in receipt of recommended care among younger versus older medicare beneficiaries: a cohort study - Ling Na; Joel E. Streim; Liliana E. Pezzin; Jibby E. Kurichi; Dawei Xie; Hillary R. Bogner; Pui L. Kwong; Steven M. Asch; Sean Hennessy (BMC, 2017)
Abstract Background Although health disparities have been documented between Medicare beneficiaries based on age (<65 years vs. older age groups), underuse of recommended medical care in younger beneficiaries has not been thoroughly investigated. In this study, we aim to identify and characterize vulnerabilities of the younger Medicare age group (aged <65 years) in relation to older age groups (aged 65-74 years and ≥75 years) and to explore age group as a determinant of use of recommended care among Medicare beneficiaries. Methods We conducted a cohort study of community-dwelling Medicare beneficiaries who participated in the Medicare Current Beneficiary Survey between 2001 and 2008 (N = 30,117). Age group characteristics were compared using cross-sectional data at baseline. During follow-up, we assessed the association between age and receipt of recommended care on 38 recommended care indicators, adjusting for sociodemographic and clinical characteristics. Follow-up periods differed by component indicator. Results At baseline, a higher proportion of younger beneficiaries experienced social disadvantage, disability and certain morbidities than older age groups. During follow-up, younger beneficiaries were significantly less likely to receive overall recommended care compared to those 65-74 years of age (adjusted odds ratio and 95% confidence interval: 0.75, 0.70-0.80). In addition, male gender, non-Hispanic black race, less than high school education, living alone, with children or with others, psychiatric disorders and higher activity limitation stages were all associated with underuse of recommended care. Conclusions Younger Medicare beneficiary status appears to be an independent risk factor for underuse of appropriate care. Support to ameliorate disparities in different social and health aspects may be warranted.